2014
DOI: 10.3390/su6107224
|View full text |Cite
|
Sign up to set email alerts
|

Local Perceptions about the Effects of Jatropha (Jatropha curcas) and Castor (Ricinus communis) Plantations on Households in Ghana and Ethiopia

Abstract: Biofuel plantations have been hyped as a means to reinvigorate Africa's rural areas. Yet there is still apprehension about the negative environmental and social impacts of large-scale commercial biofuel production around rising food prices, land grabbing, ecological damage, and disruption of rural livelihoods. Given the extent of Jatropha curcas production in Ghana and Ethiopia and Castor bean (Ricinus communis) in Ethiopia, this paper presents the results of a study that assessed the socio-economic implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Jatropha investment in Ghana generally unfolded transformations as unsatisfactory development outcomes for both investors and local communities. In a study conducted by Timko et al [26], several outcomes were identified in some selected Jatropha investment sites in Ghana. Firstly, an average of 55.5 acres of land utilized by farmers were taken over by investors for large-scale Jatropha production.…”
Section: Transformations In Ghanamentioning
confidence: 99%
See 1 more Smart Citation
“…Jatropha investment in Ghana generally unfolded transformations as unsatisfactory development outcomes for both investors and local communities. In a study conducted by Timko et al [26], several outcomes were identified in some selected Jatropha investment sites in Ghana. Firstly, an average of 55.5 acres of land utilized by farmers were taken over by investors for large-scale Jatropha production.…”
Section: Transformations In Ghanamentioning
confidence: 99%
“…This was driven by the outrageous prices of oil in the international market, a desire to ensure energy security, and the quest to reduce the emissions of harmful gases leading to climate change [1]. According to Openshaw [2], Jatropha was favored by investors because According to Timko et al [26] and Hamenoo [27], outcomes of initial Jatropha investment were negative on local land tenure systems, food production, and livelihoods. The annual output of farmers declined due to their use of parcels of land that were smaller than the ones they had access to before the large-scale Jatropha plantations were established [28].…”
Section: Introductionmentioning
confidence: 99%
“…This resesearch extents Whiteman and Mamen (2002) and Timko et al (2014) on the perceptions of communities on outcomes by investigating perceptions of both inputs and outcomes. Further, this investigation is signicant because it has not been conducted before in literature.…”
Section: Distributive Justicementioning
confidence: 82%
“…Li, Wang, Wuzhati, & Wen, 2016). Further, other negative environmental outcomes that were also reported are destruction of ecological diversity, uncontrolled bushfires, and destruction of water resources (Kusiluka et al, 2011;Obidzinski et al, 2013;Syagga & Olima, 1996;Timko et al, 2014).…”
Section: Environmental Outcomesmentioning
confidence: 94%
See 1 more Smart Citation